Measurement of single π0 production by coherent neutral-current ν Fe interactions in the MINOS Near Detector - Adamson, P; Anghel, I; Aurisano, A; Barr, G; de Jong, J; Weber, A; MINOS Collaboration (American Physical Society, 2016)
Forward single π0 production by coherent neutral-current interactions, νA→νAπ0, is investigated using a 2.8×1020 protons-on-target exposure of the MINOS Near Detector. For single-shower topologies, the event distribution in production angle exhibits a clear excess above the estimated background at very forward angles for visible energy in the range 1-8 GeV. Cross sections are obtained for the detector medium comprised of 80% iron and 20% carbon nuclei with =48, the highest- target used to date in the study of this coherent reaction. The total cross section for coherent neutral-current single π0 production initiated by the νμ flux of the NuMI low-energy beam with mean (mode) Eν of 4.9 GeV (3.0 GeV), is 77.6±5.0(stat)-16.8+15.0(syst)×10-40 cm2 pernucleus. The results are in good agreement with predictions of the Berger-Sehgal model.